Inter- and intraspecific variation in foraging ecology of sympatric fur seals Arctocephalus gazella and Arctocephalus tropicalis from Marion Island - De Bruyn, P.J. Nico (University of Pretoria, 2021)
Dissertation (MSc (Zoology))--University of Pretoria, 2021.